Implementasi Fuzzy Tsukamoto Untuk Menentukan Objek Wisata Terbaik di Kota Sabang Berbasis Web (Yayasan Kawanad, 2022)
Sabang City has the characteristics of diverse natural tourism and can be used as a tourist spot for the community. In choosing a tourist spot, it is certainly not easy, apart from distance, cost, transportation and the number of family members, it is also necessary to consider so that the selection of tourist attractions visited by the community is in accordance with their wishes and financial conditions. The purpose of this research is to apply a recommendation system using the fuzzy logic of the Tsukamoto method and a web-based programming language as the language that will be used in making a decision support system application program to determine the best tourist attraction in Aceh. The several stages of work consist of; data collection, analysis, application design and design, implementation, and testing and evaluation. The results of research and testing of the Decision Support System for Determining the Best Tourist Attractions Using the Fuzzy Tsukamoto Method in the City of Sabang Web-Based that have been carried out by the author, several conclusions can be drawn, namely; 1) The expert system application to find the best tourist attraction is an application based on rules to solve problems to determine the best tourist attraction, especially in Sabang City with a high level of accuracy and is used as a tourist reference to determine the tourist attraction to be selected, 2) With the Expert System In this case, tourists or people who need it as a reference about the best tourist objects in Sabang City and as a reference for the Sabang City Government, and 3) The results of the analysis generated from this system are the same as the results of manual calculations using the theory of the Fuzzy Tsukamoto Method so that the accuracy The results are in accordance with the calculations obtained from the trial.